ANALISIS PENGARUH FAKTOR PRODUKSI TERHADAP PRODUKTIVITAS USAHATANI KELAPA SAWIT POLA SWADAYA DI DESA SUNGAI BULUH KECAMATAN KUANTAN SINGINGI HILIR, KABUPATEN KUANTAN SINGINGI - Edward Panjaitan; Ujang Paman; Darus (UIR Press, 2020)
ABSTRACT Palm oil is one of the potential commodities that is widely cultivated by farmers in Singingi Hilir Regency. This study aims to analyze the farmers’ characteristics and profile of oil palm farming, the use of factors of production, costs, production, income and efficiency of oil palm farming, and the effect of production factors on oil palm farming productivity. The research was conducted during 6 months, starting from September 2018 to February 2019. Survey location was selected in Sungai Buluh Village Kuantan Singingi Hilir District Kuantan Singingi Regency and samples were purposively selected as 38 farmers. The samples were farmers who have oil palm farming with age between 10-15 years. Data were collected by survey method, consisting of primary data and secondary data. The results showed that the average age of farmers was 46.32 years, the education level of farmers averaged 9.61 years, the average number of family members was 4 person with having experience on oil palm cultivation was 13.84 years. The average of farmers’ land area was 3.63 ha. The average of oil palm production cost was IDR 40,227,034/year, consisting of variable costs of IDR 39,818,783 and fixed costs of IDR 408,251. The average of oil palm production in fresh fruit bunch was 64,740 kg/year with a selling price of IDR 1,449/kg and revenue was IDR 93,813,371/year. Moreover, the profit obtained was IDR 53,586,337/year and efficiency value (RCR) was 2.33. The land area and urea fertilizer had a significant effect on palm oil productivity in Sungai Buluh Village, Singingi Hilir District, Kuantan Singingi Regency. Keywords:Production factors, Oil palm farming, Productivitas, Swadya pattern.